Tax evasion through offshore companies: How important the phenomenon is? - Ginevičius, Romualdas; Tvaronavičiene, Manuela (Journal of Business Economics and Management, 2004)
The aim of the paper is to elaborate phenomenon of offshore activity. In the article principles and conditions of offshore companies’ performance have been discussed and the most popular areas of offshore economical activity analyzed. Authors’ view to efficiency of Lithuanian government’s attempts to restrict usage of offshore zones has been presented. First Published Online: 14 Oct 2010